Strategic complementarities and money market fund liquidity management - Jonathan Witmer (Bank of Canada, 2017)
Following the financial crisis, there has been increased regulatory focus on the management of liquidity in mutual funds and, specifically, whether funds hold enough liquidity to guard against the potential for investor runs. Using a novel, detailed regulatory dataset on the portfolio holdings of US money market funds, I find that internal prime money market funds - those that manage the liquidity of other funds in the fund family - have lower liquidity than external prime funds. This suggests that money market funds hold more liquidity to reduce the potential for strategic complementarities (i.e., incentives to run) in investor redemptions, because the family funds that invest in these internal funds should be able to coordinate their redemption decisions. Additionally, at quarter ends, when non-US bank dealers reduce their repo funding (Munyan, 2015), I find that prime money market funds reduce their overnight liquidity, which consists primarily of overnight repos. External prime money market funds do not let this decreased cash demand from non-US bank dealers reduce their liquidity as much as internal funds do. This all suggests that these external prime money market funds are more concerned about overnight liquidity, consistent with greater concern about potential investor strategic complementarities.
Keywords: F30; G01; G18; G20; 330; Financial markets; Financial institutions